A Frenchwoman's imperial story : Madame Luce in nineteenth-century Algeria - Rogers, Rebecca, 1959- (Stanford University Press, 2013)
Eugénie Luce was a French schoolteacher who fled her husband and abandoned her family, migrating to Algeria in the early 1830s. By the mid-1840s she had become a major figure in debates around educational policies, insisting that women were a critical dimension of the French effort to effect a fusion of the races. To aid this fusion, she founded the first French school for Muslim girls in Algiers in 1845, which thrived until authorities cut off her funding in 1861. At this point, she switched from teaching spelling, grammar, and sewing, to embroidery-an endeavor that attracted the attenti.